2014
DOI: 10.1515/jpem-2013-0387
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency in apparently healthy children in north India

Abstract: A high prevalence of clinical and biochemical VDD was noted in apparently healthy children belonging to the USES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 9 publications
1
41
3
Order By: Relevance
“…The authors noted a high prevalence (91·1 %) of vitamin D deficiency (VDD; defined as serum 25-hydroxyvitamin D (25(OH)D) level <50 nmol/l) among pre-school children in rural Nepal. Their study contributed significantly to the limited literature on VDD in apparently healthy children in the South-East Asia region (2)(3)(4)(5)(6) . Currently, both developed and developing countries are facing an unrecognized and untreated pandemic of VDD.…”
Section: Madammentioning
confidence: 96%
See 1 more Smart Citation
“…The authors noted a high prevalence (91·1 %) of vitamin D deficiency (VDD; defined as serum 25-hydroxyvitamin D (25(OH)D) level <50 nmol/l) among pre-school children in rural Nepal. Their study contributed significantly to the limited literature on VDD in apparently healthy children in the South-East Asia region (2)(3)(4)(5)(6) . Currently, both developed and developing countries are facing an unrecognized and untreated pandemic of VDD.…”
Section: Madammentioning
confidence: 96%
“…Most of these studies defined VDD as 25(OH)D level <50 nmol/l (3)(4)(5) . Among them, only a few studies also studied clinical signs suggestive of VDD (such as rachitic rosary, frontal bossing, Harrison's sulcus, wrist widening, wide anterior fontanelle, double malleolus, craniotabes and bowing of the legs) (4,5) . Tiwari and Puliyel (2) demonstrated that the prevalence of 25(OH)D level <35 nmol/l was 84 % in slum children from three areas in Delhi.…”
Section: Madammentioning
confidence: 99%
“…This study contributed significantly to the limited literature on VDD in apparently healthy children in India. [234]…”
mentioning
confidence: 99%
“…[4] On univariate analysis, VDD was associated with relatively younger age group, female sex, failure to thrive, exclusive breastfeeding, inadequate sun exposure, and no Vitamin D supplements. [4]…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Studies from India have reported a deficiency ranging from 30% to as high as 100%. 13,15,16 Other parts of the world like the Middle East, China and South America have also reported alarmingly high incidence of Vit D deficiency. The question that comes to our mind is whether these alarming deficiency states are related to any disease conditions; the answer to which is controversial in the present scenario.…”
mentioning
confidence: 99%